Subcutaneous Panniculitis-Like T-Cell Lymphoma (SPTL) in a Child with Spontaneous Resolution - Achiléa L. Bittencourt; Maria das Graças Silva Vieira; Eny Guimarães Carvalho; Celeste Cunha; Iguaracyra Araujo (Case Reports in Oncological Medicine)
Subcutaneous panniculitis-like T-cell lymphomas (SPTLs) α/β are rare in childhood. The present report refers to a case of a 7-year-old male child presenting an extensive skin lesion that began when he was 5 years of age. Two biopsies were evaluated using the CD3, CD4, CD8, CD56, βF1, and TIA markers. A dense infiltrate of CD3+, CD4−, CD8+, CD56−, βF1+, and TIA+ pleomorphic lymphocytes was found in the subcutis. The previous biopsy showed cytophagic histiocytic panniculitis with a small focus on CD8+ and βF1+ malignant cells. The lesion regressed spontaneously. This case shows that prognosis may be excellent in SPTL (α/β). On the other hand, it also serves as an alert that a biopsy performed in an area of cytophagic panniculitis may lead to misdiagnosis.